Towards certified carbon footprints of products - a road map for data production : Climate Bonus project report (WP3) - Usva, Kirsi (VATT-tutkimuksia, 2009)
Yhteenveto.
Keywords: tuotteet; elinkaariarviointi; sertifiointi; kasvihuonekaasut; päästöt; hiilijalanjälki